The Influence of Mentoring on Teachers Performance in Reading Instruction for Dyslexia Children - Irdamurni; Kasiyati; Zulmiyetri; Johandri Taufan (Fakultas Ilmu Pendidikan)
The article aims to identify the influence of mentoring on teachers’ performance in conducting the class for dyslexia children in elementary school. The subjects of research were 18 teachers of class I to class VI at inclusive elementary school. The data collected using observation and interviews as well as document analysis of the teachers performance in the learning process for dyslexia children. The study includes identification and assessment, curriculum development at inclusive school; lesson plans ( RPP) modification and learning strategies in reading instruction for dyslexia children. This research used a descriptive qualitative approach. The results showed that the teachers’ performance in reading instruction for dyslexia children has improved after mentoring on reading for dyslexia children was given.